Hubungan Nilai Praktik Kerja Industri (PRAKERIN) terhadap Minat dan Sikap Belajar Siswa Kelas XII Teknik Pemesinan di SMK Dhuafa Padang - Guci, Taufik; Syahril, Syahril (ARZUSIN, 2024)
Industrial work practice (PRAKERIN) is one of the applications of teaching methods in the form of field work, students are placed directly in the business world and the industrial world. This study aims to analyze the relationship that exists from the value of industrial work practice (PRAKERIN) with interest in learning and learning attitudes of XII grade students of Mechanical Engineering at SMK Dhuafa Padang. The type of research used in this study is correlational quantitative research. This study has three variables that will be analyzed. The three variables will be examined and analyzed to determine the relationship between the independent variable (X) and the dependent variable (Y). Industrial work practice (PRAKERIN) as an independent variable (X), Learning Interest (Y1) and Learning Attitude (Y2) as dependent variables. The method used is associative quantitative research method. Quantitative data in this study are the results of the answers to the student respondent questionnaire from class XII of the machining expertise program at SMK Dhuafa Padang. Based on the research results obtained by researchers, the following conclusions can be drawn. 1) There is a positive relationship between the value of industrial work practice (PRAKERIN) and student interest in learning at SMK Dhuafa Padang. 2) There is a positive relationship between the value of industrial work practice (PRAKERIN) and students' learning attitudes at SMK Dhuafa Padang. 3) There is a positive relationship between the value of industrial work practice (PRAKERIN) with students' interest in learning and learning attitudes at SMK Dhuafa Padang.